Harnessing dairy wastewater to cultivate Scenedesmus sp. for biofertilizer applications in Phaseolus vulgaris L.: a sustainable agro-biotechnological approach - Álvarez-Montero, Xavier; Mercado-Reyes, Ingrid; Castillo-Chamba, Wiliam; Santos-Ordóñez, Efrén (Frontiers in Plant Science, 2025)
Transforming traditional linear production into sustainable circular processes is crucial, and integrating microalgae biomass production with wastewater recycling is a promising approach. This study addresses key challenges using dairy industry effluents as a nutrient-rich medium, achieving high biomass productivity and protein content with Scenedesmus sp. grown in an 80% wastewater-based medium. Impressive nutrient removal efficiencies were recorded for TN (79.24%) and PO4-3 (77.14%). The proposed culture medium achieved maximum productivity of 0.22 ± 0.05 g L−1 day−1 and a high protein concentration of 384.38 ± 34.06 mg g−1, demonstrating the medium’s efficiency in promoting substantial biomass and nutritional quality. The application of Scenedesmus sp. biomass in treatment T1 (extract) and T2 (culture) in Phaseolus vulgaris significantly improved soil quality, increasing the concentration of organic matter (SOM), nitrates, phosphates, and microbial activity. Additionally, T1 promoted the vegetative and reproductive development of P. vulgaris, as reflected in a germination index of 305.81%, an average height of 49.52 cm, higher leaf density, a greater number of floral buds, and enhanced floral development. These results demonstrate the bio-stimulatory potential of biomass and its role in practical bioremediation, highlighting the environmental and agricultural benefits of this innovative approach.